The Effects of Heat Exposure on Human Mortality Throughout the United States. (4th April 2020) - Shindell, Drew; Zhang, Yuqiang; Scott, Melissa; Ru, Muye; Stark, Krista; Ebi, Kristie L.
Abstract: Exposure to high ambient temperatures is an important cause of avoidable, premature death that may become more prevalent under climate change. Though extensive epidemiological data are available in the United States, they are largely limited to select large cities, and hence, most projections estimate the potential impact of future warming on a subset of the U.S. population. Here we utilize evaluations of the relative risk of premature death associated with temperature in 10 U.S. cities spanning a wide range of climate conditions to develop a generalized risk function. We first evaluate the performance of this generalized function, which introduces substantial biases at the individual city level but performs well at the large scale. We then apply this function to estimate the impacts of projected climate change on heat‐related nationwide U.S. deaths under a range of scenarios. During the current decade, there are 12, 000 (95% confidence interval 7, 400–16, 500) premature deaths annually in the contiguous United States, much larger than most estimates based on totals for select individual cities. These values increase by 97, 000 (60, 000–134, 000) under the high‐warming Representative Concentration Pathway (RCP) 8.5 scenario and by 36, 000 (22, 000–50, 000) under the moderate RCP4.5 scenario by 2100, whereas they roughly double under the aggressive mitigation scenario RCP2.6. These results include estimates of adaptation that reduce impacts by ~40–45% as well as population increases that roughly offset adaptation. The results suggest that the degree of climate change mitigation will have important health impacts on Americans. Key Points: We develop a generalized risk function from U.S. epidemiological data to quantify nationwide heat‐related premature deaths We find ~12, 000 premature deaths annually in the contiguous United States during the 2010s Projected deaths rise to ~110, 000 and ~50, 000 year −1 under high‐ and moderate‐warming scenarios, respectively, including population growth